Pengaruh Volume Perdagangan Saham, Leverage, dan Kebijakan Dividen Terhadap Volatilitas Harga Saham - Mario Ascaryo Septyadi; Theresia Hesti Bwarleling (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to determine the influence of Stock Trading Volume, Leverage, and Dividend Policy both simultaneously and partially from LQ45 Index companies listed on the Indonesia Stock Exchange in 2016-2018. The analysis technique used is multiple linear regression analysis using the IBM SPSS 26 program. This type of research is a quantitative study using secondary data, there are 18 companies as a sample of research data collected by purposive sampling technique. The dependent variable in this study is Stock Price Volatility, while the independent variables are Stock Trading Volume, Leverage, and Dividend Policy. The results showed that partially Stock Trading Volume has a positive and significant effect on Stock Price Volatility. Leverage and Dividend Policy have no significant effect on Stock Price Volatility. It is expected that the results of this study can be taken into consideration for investors to choose the right type of investment based on the level of stock price volatility that is influenced by various factors, especially stock trading volume..